2010
DOI: 10.1007/s10689-010-9334-9
|View full text |Cite
|
Sign up to set email alerts
|

Lynch syndrome: the influence of environmental factors on extracolonic cancer risk in hMLH1 c.C1528T mutation carriers and their mutation-negative sisters

Abstract: Lynch Syndrome (LS) is a cancer susceptibility syndrome caused mostly by mutations in the mismatch repair genes, hMLH1, hMSH2 and hMSH6. Mutation carriers are at risk of colorectal and endometrial cancer and, less frequently, cancer of the ovaries, stomach, small bowel, hepatobiliary tract, ureter, renal pelvis and brain. The influence of environmental factors on extracolonic cancer risk in LS patients has not been investigated thus far. The aim of this study was to investigate some of these factors in South A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Similarly, we did not observe statistically significant association between endometrial cancer risk and age at first and last live birth in Lynch syndrome, which is in line with some 13, 35 but not all studies 35, 36 conducted in the general population. 37 The lack of an observed association between endometrial cancer risk and PMH use in this study could be attributed to lack of statistical power (only 2.8% reported use of estrogen-only and 4.3% reported use of combined estrogen and progesterone for at least one year). Additional unmeasured confounding or information bias could also account for this finding.…”
Section: Discussionmentioning
confidence: 60%
“…Similarly, we did not observe statistically significant association between endometrial cancer risk and age at first and last live birth in Lynch syndrome, which is in line with some 13, 35 but not all studies 35, 36 conducted in the general population. 37 The lack of an observed association between endometrial cancer risk and PMH use in this study could be attributed to lack of statistical power (only 2.8% reported use of estrogen-only and 4.3% reported use of combined estrogen and progesterone for at least one year). Additional unmeasured confounding or information bias could also account for this finding.…”
Section: Discussionmentioning
confidence: 60%
“…Clinicopathological characteristics of the patients with HNPCC related to endometrial cancer HNPCC in Koreans are similar to those in Americans and Europeans,9,12 such as diabetes, age of menarche, menopause status, parity, histology, FIGO stage, and tumor grade.…”
mentioning
confidence: 75%
“…A number of tumor-related events are involved in this process, including oncogene activation, tumor suppressor gene inactivation, mismatch repair (MMR) gene mutations and gene promoter hypermethylation ( 1 , 2 ). Since the identification of MMR genes, studies have investigated the association between the aberrant expression of MMR genes and hereditary nonpolyposis colorectal cancer (HNPCC) or sporadic colorectal cancer ( 3 5 ). A number of studies have found that aberrant MMR gene expression plays an important role in the occurrence of colorectal cancer ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%